2019
DOI: 10.1111/1750-3841.14652
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antibacterial Activity and Subacute Toxicity of a Quercus crassifolia Polyphenolic Bark Extract for its Potential Use in Functional Foods

Abstract: Oak wood is used in barrels for wine aging. During aging, polyphenols are transferred from the barrels to the liquid. Although the bioactivity of oak polyphenols in wines has been extensively studied, no investigation exists on their toxicological properties, which limits their use as functional safe ingredients for other products. In this work, the chemical composition of a polyphenolic extract of Quercus crassifolia bark (QCBe) was studied by GC‐MS. Its antibacterial properties on probiotic and pathogenic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
7
1
Order By: Relevance
“…barks. This activity hints towards the presence of polyphenols in the mentioned extracts [ 5 , 6 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 97%
“…barks. This activity hints towards the presence of polyphenols in the mentioned extracts [ 5 , 6 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 97%
“…At present, the increase of AMR in clinical drugs and the lack of new antibiotics to resist the emerging drug-resistant strains have become the main problems of human health in this century (Moellering et al 1976;Sovari et al 2020). To eliminate the harm in the future use of drugs, researchers are gradually seeking for antibacterial ingredients from natural products (Valencia-Aviles et al 2019;Sanchezzarate et al 2020;Zhang et al 2020), especially those plants which have been used for antibacterial substance since ancient times (Selseleh et al 2020;Dereje et al 2021;Frankova et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate the harm in the future use of drugs, researchers are gradually seeking for antibacterial ingredients from natural products (Valencia‐Aviles et al . 2019; Sanchez‐zarate et al . 2020; Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we found that a purified extract from Quercus crassifolia bark is a good source of polyphenols (860.39 ± 5.68 mg GAE/g) with a higher in vitro free radical scavenging ability toward reactive species of biological importance (hydroxyl and peroxyl radical and the superoxide anion) [18]. Moreover, in another study, we tested the antibacterial activity and subacute-oral toxicity of the oak bark's phenolic extract, in order to understand the potential impact of its addition to fermented foods as a functional ingredient [19].…”
Section: Introductionmentioning
confidence: 99%